Visual in advertising / Noor Atheerah Redza Rezduan - Rezduan, Noor Atheerah Redza (Faculty of Art and Design, 2020)
Advertising has many different uses: to create and promote the image of a company. product. or brand, to make announcements. to make sales, or to support a cause. The main goal of advertising is persuasion. It relies heavily on promoting products and services. Charitable causes. individuals such as politicians and celebrities. as well as Ideas. As a marketing communication tool. advertising is an essential element in the mile of integrated marketing Communications. Advertising also provides users with Information that allows them to differentiate between products. It enables businesses to bring new products to the attention of consumers enough to keep them in business. In this way, it energizes the engine of people's economy (Cartwright. S.,2016). By contrast, visual advertising doesn't always sell products directly. Sometimes it sells ideas, visions or even fantasies related to what the brand has to offer. Ad designers and creatives rely on several tactics to optimize their visual advertising success and success. Some of these approaches may seem technical, but there is still a lot of psychology involved. For example. Psychological problems in the way colour set the mood, how the language of the character supports the message. And how symbols are used to representatives or ideas.